Exploratory review on the effect of Astragalus mongholicus on signaling pathways - Xu Lou, Inmaculada; Yu, Xinyi; Chen, Qilan (Frontiers in Pharmacology, 2024)
BackgroundAstragalus mongholicus Bunge [Fabaceae; Astragali radix] (AM), a traditional Chinese medicinal (TCM) botanical drug, has been used for centuries and is gaining growing recognition in medical research for its therapeutic potential. The currently accepted scientific name is Astragalus mongholicus Bunge, with Astragalus membranaceus Fisch. ex Bunge recognized as a taxonomic synonym. This review explores the most relevant scientific studies on AM, focusing on its chemical composition, mechanisms of action, and associated health benefits.Main bodyAM is commonly used in clinical practice to treat diabetes mellitus, cardiovascular diseases, oncological processes, lipid metabolism disorders, and ulcerative colitis. Recent research has investigated its potential as a product for anti-aging purposes. These therapeutic effects are attributed to the interactions of bioactive metabolites such as Astragaloside IV, Formononetin, and polysaccharides, with various signaling pathways, leading to the activation or inhibition of gene expression. This review aims to map the signaling pathways affected by these metabolites and their effects on different pathologies. Studies suggest that these metabolites act on signaling pathways such as TLR4/MyD88/NF-κB, PI3K/AKT, RNA expression, and tumor receptors. However, further research is necessary to validate the findings in human trials with better methodological quality.ConclusionAM is rich in bioactive metabolites that interact with various signaling pathways, modulating diseases such as diabetes mellitus type 2, cardiovascular diseases, cancer, lipid metabolism disorders, and ulcerative colitis. Although promising, the majority of the studies are conducted in vitro and animal models, and more rigorous human trials are needed to determine the therapeutic potential of AM.